Molecular Structure, Thermochemistry, Non-Covalent Interactions Computation Using DFT Studies Of The 1 Amino 2-(3,4- Dihydroxyphenyl) Boronic Acid (AHPEBA) Compound - Kareem, Rebaz Obaıd (Niyazi BULUT, 2024)
Theoretical parameters for 1 amino 2-(3,4- dihydroxyphenyl) boronic acid in AHPEBA were investigated using density functional theory (DFT), and STO-3G basis set. Quantum chemical calculations were done on the link between inhibitor molecular structure, chemical reactivity, stability, and inhibition performance. In addition, we investigate the theoretical foundations of AHPEBA by looking at properties and characteristics such as the Highest Occupied Molecular Orbital (HOMO), the Lowest Unoccupied Molecular Orbital (LUMO), the Band Gap (BG), the Density of States (DOS), the Ultraviolet (UV) properties, and the Natural Bond Orbital (NBO) evaluations. Also, we use the reduced density gradient (RDG) method to explore non-covalent interactions (NCI). The fact that the BG was measured to be -5.85043 eV lent credence to the hypothesis that the molecule had a high level of chemical stability and a low level of chemical reactivity. According to molecular hardness and softness, electronegativity, and chemical potential, the molecule C8H12BNO4 has a high degree of chemical stability, and a low degree of reactivity. This is the first theoretical study of the AHPEBA compound.
Keywords: Materials Engineering (Other); Malzeme Mühendisliği (Diğer)